Investigating differences in self-compassion levels: effects of gender and age in a Greek adult sample - Eirini Karakasidou; Georgia Raftopoulou; Anastassios Stalikas (Ψυχολογία: το Περιοδικό της Ελληνικής Ψυχολογικής Εταιρείας, 2020)
Self-compassion is a recently developed construct of positive psychology. Several studies have shed light on their benefits on people’s psychological well-being. Furthermore, studies have focused on examining changes in self-compassion according to gender, in specific age groups, demonstrating inconsistent results. The present study aimed to investigate the interaction between self-compassion and gender, overtime, in a wide age range of adulthood. The sample consisted of 291 participants, age range between 18 and 72 years of age, of the general population. The participants completed online self-report questionnaires of the Self-Compassion Scale (SCS) (Neff, 2003b). Overall results revealed that self-compassion levels were higher for men than women. In addition, self-compassion was positively correlated with age, while older men, of 50 years and above, demonstrated higher self-compassion levels compared to younger age groups. The findings suggest the prudence of self-compassion on psychological prosperity. It is also proposed that the outcomes could contribute to the design of more informed, structured, and well-established intervention planning, targeting groups according to age and gender, which appear to be the most vulnerable. Finally, probable suggestions for further investigation are considered.